Isolation and Identification of Bacteria that Has Potential as Producer of Protease Enzyme in the Tannery Industry, PT. Adi Satria Abadi (ASA), Yogyakarta - M. I. Said; J. C. Likadja (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2012)
Bacteria are one of the microorganisms that have the potential as a producer of protease enzyme. Tannery industrial waste is one of the media predicted to contain a number of proteolytic bacteria because of the waste generated is composed largely of protein and fat which are good as growing medium for bacteria. This study aimed to isolate and identify bacteria that have the potential as a producer of protease enzyme. Research conducted at the waste water processing installation (WWPI), tannery industry of PT.Adi Satria Abadi (ASA), Sitimulyo, Bantul, Yogyakarta and Laboratory of Animal Product and Food, Faculty of Animal Science, Gadjah Mada University, Yogyakarta. Solid waste (SW), waste water (WW) and soil (S) around the industry are used as source of isolates. Random screening methods used for isolation and identification. The results obtained by isolation and identification of 1264 colonies (621 colonies from the SW, 156 of the WW and 487 of S). Thirty one colonies (2.5%) were identified as potentially proteolytic bacteria by the presence of clear zone (halo) around the colony while the 1.233 colonies (97.5%) were not potential. The third colony isolates look like a white crust, firmly attached to the medium, round, white to resemble wool and convex. Bacterial isolates from the S and SW at pH 10 and 12 were potential as a source of proteases with Proteolytic Index (PI)≥3, while the one isolated from WW was less potential.